ANALISIS DAN PERANCANGAN SISTEM INFORMASI PELAPORAN KERJASAMA DALAM & LUAR NEGERI DENGAN METODE END USER DEVELOPMENT - Riki Faza (INFOKOM (Informatika & Komputer), 2020)
An MoU is a legal action of one party (legal subject) to state its intention to the other party for something that is offered or owned. In other words, the MoU is basically a preliminary agreement, which regulates and provides an opportunity for the parties to conduct a feasibility study first before making a more detailed agreement and binding on the parties in the future. The aim of this research is to make an analysis and design of the MoU documentation system that was made and agreed upon. So that some common problems that occur such as disorganized documentation, the follow-up of the MoU is not coordinated, the parties that need information related to the MoU do not get the full information, and the reporting of work programs resulting from the MoU is not accommodated, can be resolved. Approach method to the problems of analyze system development using the End User Development method, which means Computer-based system development strongly engages application users by prioritizing feedback from users during the system development cycle